Adaptação cultural e investigação das propriedades psicométricas da Barratt Impulsiveness Scale (BIS-11) - Alina Gomide Vasconcelos (2012)
Impulsivity has been fractionated into multiple independent, but correlated, components. Personality and neuropsychological studies have consistently shown its multidimensionality nature. Each of this theoretical approach use different techniques such as self-report questionnaires and neuropsychological tests to assess impulsivity, respectively. Our main objective was to investigate if there were convergent validity evidences for impulsivity as assessed by both type of measures. We administered the BIS-11 questionnaire and two neuropsychological tests (Iowa Gambling Task and Continuous Performance Test) to 266 participants to measure inhibition control and non- planning impulsivity dimensions. Results from exploratory factorial analysis and group comparison indicated there were little convergent validity evidences for overlapping between the two types of measures. These findings were discussed in tenns of impulsivity as a multi-factorial construct and even instruments specificities to assess it. Implications for psychological theory and impulsivity assessment were also proposed.